Semiochemical Diversity in Practice: Antiattractant Semiochemicals Reduce Bark Beetle Attacks on Standing Trees—A First Meta-Analysis. (22nd August 2012) - Schlyter, Fredrik
Abstract : Reduction of tree mortality caused by bark beetle attacks is not only important for forestry, but also essential for the preservation of biodiversity and forest carbon sinks in the face of climate change. While bark beetle mass trapping (a "pull" approach) is implemented in practice, few studies exist to estimate its effect. The more complex "push-pull" tactic has, in contrast, been repeatedly tested during the last decade. I analysed published data from 32 experiments in 9 papers published during 2000–2011 on Ips typographus and Dendroctonus ponderosae, to test if there was an overall effect of antiattractant semiochemicals, that is, if treatments reduced the number of attacks on standing trees at the habitat or stand scale. This meta-analysis showed a substantial overall effect size (treatment-control means divided by their SD) of −0.96, with some heterogeneity but little evidence of publication bias. There was no effect of beetle species or publication year. Heterogeneity resulted from different designs and beetle population levels (as year of study). The conventional "% Reduction" measure correlated well with effect size (r 2 = 0.7 ). Recommendations include more precise reporting of responses (avoiding dichotomous data), more unified experimental designs, and further meta-analyses that include "grey literature" and more beetle species.